You Can’t Live Alone: Spatial Climate Change Shock and Economic Growth in the Largest Archipelagic State - Khaliq, Abdul; Karimi, Syafruddin; Taifur, Werry Darta; Ridwan, Endrizal (International Journal of Energy Economics and Policy, 2025)
This study explores the effect of province-specific temperature and precipitation, which are expressed as deviancies of temperature and precipitation from historical data using the spatial Mankiw, Romer, and Weil (MRW) growth model. Performing a panel data set of 34 provinces covering the period from 2006 to 2022, this study predicts the nonlinear impact of climate change on per capita real output growth. We also show the inverted U-shaped curve from persistent changes in the temperature and precipitation on per capita real output growth either above or below its historical data. In the absenteeism of mitigation strategies, we found that an insistent increase in the average temperature or precipitation per year diminishes per capita real output growth. This study also explores climate change’s spatial impacts on economic growth performance through spatial lambda and rho parameters. We discovered the significant provincial spillover effect of climate change on economic growth. We also identify that increasing temperature and precipitation in provincial neighbors further decreased economic growth. Furthermore, this study conducts a robustness test by employing an open economy to meet the consistency of the baseline model. We reconfirm the empirical results of the baseline model.